How much of the future mortality toll of smoking can be avoided?. Issue 4 (16th June 2020) - Warner, Kenneth E; Mendez, David
Abstract : Objective: To determine how much future smoking-related mortality in the USA can be prevented, recognising that some of that future mortality results from past smoking. Methods: Employing a dynamic population simulation model, we estimate smoking's expected mortality burden in the USA, measured as life-years lost (LYL), in a status-quo scenario run from 2018 through 2100. We then estimate LYL attributable to past smoking assuming that all smoking ceases at the end of 2017. We calculate the potential avoidable LYL, which we call the maximum potential reduction in premature mortality (MPRPM), as the difference between the two. We use data from the US Census Bureau, National Vital Statistics Reports, the National Health Interview Survey and Cancer Prevention Study II. Results: Under status-quo assumptions, smoking will claim 305 million LYL in the US from 2018 to 2100. If all smoking ceased at the end of 2017, past smoking would be responsible for 191.8 million LYL. Thus, avoidable LYL by 2100—the MPRPM—would be 113.2 million, 37% of the expected toll of smoking. A sensitivity analysis finds that were the annual smoking initiation rate 3% instead of 7.8%, the MPRPM would be 13-14% lower. Were the annual permanent smoking cessation rate twice our status-quo estimate of 4.35%, the MPRPM would be 38-39% lower. Conclusions: Public health can address only the future toll of future smoking. Smoking's MPRPM is the reduction in the mortality burden of smoking that tobacco control can strive to achieve.